Feasibility of deep brain stimulation for controlling the lower urinary tract functions: An animal study. Issue 12 (December 2017) - Chen, Shih-Ching; Chu, Pei-Yi; Hsieh, Tsung-Hsun; Li, Yu-Ting; Peng, Chih-Wei
Highlights: This study systematically explored deep brain stimulation (DBS) for controlling bladder functions in rats. Pedunculopontine tegmental nucleus (PPTg) DBS could stably evocate and inhibit bladder activity. PPTg might be a promising DBS target for developing new approaches to treat bladder dysfunctions. Abstract: Objective: To evaluate the feasibility of deep brain stimulation (DBS) and compare the potential of four DBS targets in rats for regulating bladder activity: the periaqueductal gray (PAG), locus coeruleus (LC), rostral pontine reticular nucleus (PnO), and pedunculopontine tegmental nucleus (PPTg). Methods: A bipolar stimulating electrode was implanted. The effects of DBS on the inhibition and activation of micturition reflexes were investigated by using isovolumetric intravesical pressure recordings. Results: PAG DBS at 2–2.5 V, PnO DBS at 2–2.5 V, and PPTg DBS at 1.75–2.5 V nearly completely inhibited reflexive isovolumetric bladder contractions. By contrast, LC DBS at 1.75 and 2 V slightly augmented reflexive isovolumetric bladder contractions in rats. DBSs on PnO and PPTg at higher intensities (2.5–5 V) demonstrated a higher success rate and larger contraction area evocation in activating bladder contractions in a partially filled bladder. DBS targeting the PPTg was most efficient in suppressing reflexive isovolumetric bladder contractions. Conclusion: PPTg DBS demonstrated stable results and high potency for controlling bladder contractions. PPTg might be a promising DBS target for developing new neuromodulatory approaches for the treatment of bladder dysfunctions. Significance: DBS could be a potential approach to manage bladder function under various conditions.